Pengaruh Media Film “Ranah 3 Warna” Dalam Bimbingan Kelompok Untuk Meningkatkan Kemampuan Komunikasi Interpersonal Siswa Sekolah Menengah Atas - Naufal Rakha Kusuma; Aniek Wirastania (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
This study aims to evaluate the impact of utilizing Ranah 3 Warna film media in group guidance services on enhancing students' interpersonal communication skills at SMA Hang Tuah 4 Surabaya. The research employs a quantitative approach with a pre-experimental design of the one-group pretest-posttest type.The study subjects consisted of four 11th-grade students at SMA Hang Tuah 4 Surabaya who had low interpersonal communication skills. Data was collected through questionnaires and documentation, then analyzed using the Wilcoxon nonparametric statistical test with the assistance of SPSS version 26.0.Based on the research findings, the Ranah 3 Warna film media has been proven effective in improving students' interpersonal communication skills through group guidance services.. Using a quantitative approach and pre-experimental design, this research shows that after intervention with film media, there was a significant increase in students' interpersonal communication skills. These findings indicate that using film as a medium in group guidance can be an effective method for helping students develop their communication skills)